Analisis Tata Kelola Teknologi Informasi pada Layanan Infrastruktur Jaringan RSUD Provinsi NTB menggunakan COBIT 4.1 - Indri Rahmawati Yunus; Nadiyasari Agitha; Sri Endang Anjarwani Anjarwani (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
By utilizing IT network infrastructure services optimally, the use of information systems and other IT activities in RSUD Provinsi NTB will run smoothly. However, there are some problems such as devices acquisition, maintenance and network infrastructure security that must be overcome to achieve the best services in accordance with the vision and mission. This research uses COBIT 4.1 framework and maturity level as a metric of current conditions and expected conditions in RSUD Provinsi NTB. This observation results that the current maturity level is 3 and is expected to be 5. We also propose some recommendations for improvements that are expected to overcome the faced problem and make improvements to the existing IT network infrastructure service.